El Casino de Madrid, orígenes y primera andadura. - Zozaya-Montes, Maria (2013)
Here is widely studied the process of birth of a social institution which was spread all around Europe between 1830 and 1850. A study case is carried out, concretized in the Casino of Madrid, fist Casino elite Club in Spain which born in 1836. Studying deeply the associational context in Europe and Spain, we explain the causes and meanings of its origins in the country, and the explanation of the first period of developing of that association absolutely linked with the emergence of the gentlemanly capitalism elite.